PENGARUH CITRA MEREK DAN PERSEPSI LABEL HALAL TERHADAP MINAT PEMBELIAN ULANG PRODUK KOSMETIK ZOYA MALANG - Illiatus Soleha; Rois Arifin; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe purposes of this study are to find out and analyze: (1) The influence of brand image toward the product re-purchase intention. (2) The influence of halal label perception toward repurchase intention. (3) The influence of brand image and halal label toward repurchase intention. This study used descriptive quantitative research. The population of this study are the customers of zoya product in Malang by the sampling of female customers who had purchased the and the customers who had consumed the product. The accidental sampling used convenience sampling with the amount of respondent are 95. This study used multiple linear regression analysis. The result of this study are as follows: (1) Brand image positively and significantly influence on the repurchase intention with tcount 3,946 and significant value is 0,000 (2) Halal label perception positively and significantly influence on the repurchase intention with tcount 4,262 and significant value is 0,000. (3) Simultaneously, brand image and halal label positively and significantly influence on the repurchase intention with Fcount 41,756 and significant value is 0,000. Keywords: Brand image, halal label perception, Repurchase intention